Brivaracetam Disposition in Mild to Severe Hepatic Impairment. (3rd May 2013) - Stockis, Armel; Sargentini‐Maier, Maria Laura; Horsmans, Yves
Abstract Brivaracetam is a high‐affinity synaptic vesicle protein 2A (SV2A) ligand in clinical development for epilepsy. This open‐label, single‐dose study evaluated brivaracetam disposition in participants with different degrees of hepatic impairment versus matched healthy controls. Twenty‐six participants (38–72 years; 19 males and 7 females) with hepatic impairment classified by Child‐Pugh score (mild, n = 6; moderate, n = 7; severe, n = 7) or normal hepatic function (n = 6) received a single oral dose of 100 mg brivaracetam. The pharmacokinetics of brivaracetam and its three main metabolites (acid, hydroxy, hydroxyacid) were determined and correlated with impairment severity. Dynamic liver function tests correlated with hepatic impairment severity. The plasma half‐life of brivaracetam was 9.8, 14.2, 16.4, and 17.4 hours and the area under the plasma concentration‐time curve was 29.7, 44.6, 46.7, and 47.1 µg h/mL in healthy controls and participants with mild, moderate, and severe liver impairment, respectively. Production of the acid metabolite was increased and the hydroxylated metabolites were decreased in participants with hepatic impairment versus healthy controls. Exposure to brivaracetam increased by 50–60% in patients with hepatic impairment, irrespective of severity. The relative importance of biotransformation pathways was altered; cytochrome P450 (CYP)‐dependent hydroxylation decreased; CYP‐independent acid metabolite formation increased concomitantly.